Appreciating literature (Mission Hills, Calif. : New York : Glencoe Pub. Co., McGraw-Hill, 1991)
Presents twenty-seven oral interpetations of short stories, poems, nonfiction, and drama, from various historical periods. Includes works by Cather, Chekhov, Saki, Dickinson, Shakespeare, Poe, and others. Primarily geared for classroom learning.
"Scribner literature audiotapes."
In container (25 cm.)
Read by professional actors or by the authors themselves.
Keywords: Literature -- Collections; Oral interpretation